2012
DOI: 10.1166/jbt.2012.1041
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Mineralized Collagen as a Bone Graft Substitute for Anterior Cervical Intersomatic Fusion

Abstract: Although autograft is a routine procedure in anterior interbody fusion of the cervical spine, donor site morbidity is a significant problem. Many bone grafting materials developed such as allograft bone, demineralized bone matrix (DBM), and synthetic implants were used to repair bony defects; however, each has its specific disadvantage. Therefore, alternative materials for autogenous bone in grafting are needed. Ninety-one patients with symptomatic cervical disc diseases were randomly allocated for either auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
(35 reference statements)
0
28
0
Order By: Relevance
“…In the outermost superficial zone collagen fibrils are oriented parallel to the articulating surface and in the middle and calcified zones, the collagen fibrils are random and perpendicular. COL has been widely used in cartilage tissue engineering due to its excellent biocompatibility, negligible immunogenicity, cell adhesion and biodegradability [18,19]. COL can also specifically interact with growth factors which promote cell ingrowth and remodelling [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the outermost superficial zone collagen fibrils are oriented parallel to the articulating surface and in the middle and calcified zones, the collagen fibrils are random and perpendicular. COL has been widely used in cartilage tissue engineering due to its excellent biocompatibility, negligible immunogenicity, cell adhesion and biodegradability [18,19]. COL can also specifically interact with growth factors which promote cell ingrowth and remodelling [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] Cell culture and animal model tests showed that the composite material was highly osteoconductive, biocompatible, and bioresorbable. [33][34][35] Cell culture and animal model tests showed that the composite material was highly osteoconductive, biocompatible, and bioresorbable.…”
Section: Introductionmentioning
confidence: 99%
“…The nHAC/PLA, produced by Beijing Allgens Medical Science & Technology Co., Ltd., is attractive as bone substitute because the novel biomimetic strategy used to generate it provides properties similar to natural bone. [33][34][35] Cell culture and animal model tests showed that the composite material was highly osteoconductive, biocompatible, and bioresorbable. [36][37][38] Our previous study has demonstrated that the nHAC/PLA can be served as a good scaffold for autologous rabbit DPSCs seeding, proliferation and differentiation, and can induce transplanted DPSCs to reconstruct rabbit alveolar bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive vitro and animal studies have that demonstrated MC has excellent biocompatibility, biodegradability, high osteoconducitive activity, and promotes bone repair and regeneration. [10][11][12] Recently MC has been evaluated in spinal fusion. In a series of 91 patients who underwent two-or three-level ACDF with rigid anterior plate fixation with either autologous or MC, the results demonstrated 95.7% fusion rate for MC with results comparable to those with autologous bone which was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vivo preclinical and clinical trials have shown MC is a safe and promising substitute for autologous iliac crest bone graft. [10][11][12] It has now been approved by the China Food and Drug Administration as a class III medical device.…”
Section: Introductionmentioning
confidence: 99%